Effects of magnetically treated water on properties of concrete - Engin, Yasin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
The aim of this thesis is to investigate the effects of magnetic field on water properties and the effects of magnetically treated water on concrete properties. For this reason a device was set up to prepare treated water. Permanent neodymium magnets were located around a PVC pipe and it was used to create treated water and admixture. To investigate the effects of magnetic field on water properties pH, Surface Tension, viscosity, FTIR and NMR tests were conducted. To determine the effects of magnetically treated water on concrete properties 32 concrete mixtures were prepared. The variables of concrete mixtures were the treatment of water, type of admixtures, treatment of admixtures and cement dosage. For 24 concrete mixtures the recipes were same. 4 concrete mixtures were produced without admixtures and 4 mixtures were produced at same workability level with different water/cement ratios. It was aimed to determine the effect of magnetically treated water on workability and strength of concrete. Also rapid chloride ion permeability test and water penetration under pressure test were carried out to investigate the influence of water treated by magnetization on durability of concrete. The experiments were conducted at Bo˘gazi¸ci University Construction Materials Laboratory, Sabancı University Biochemistry and Nuclear Research Laboratory and Ak¸cansa Cement Technology Center. Results showed that magnetization can change the properties of water such as increase in pH and viscosity, decrease in Surface Tension, change in hydrogen bond strength and decrease in size of water clusters. On concrete side, it was found that there can be an enhancement in workability of concrete when treated water or admixture is used and the improvement in workability can lead to a decrease in water amount used in concrete production and an improvement in compressive strength.
Keywords: Magnetic fields.